A Erdogan’s Construct of Islamism in the Normalization of Turkiye-Israel Policy 2016 - Ammar Aminudin (Mediasi: Journal of International Relations, 2022)
Türkiye and Israel as actors in international relations have had a long-standing relationship of ups and downs. At the beginning of his leadership, Erdogan also established cooperation with Israel. However, the Three Weeks Attacks on Palestine and the Mavi Marmara Tragedy have brought relations between the two countries to their lowest point. Finally, Erdogan normalized relations with several conditions that must be met by Israel in 2016. The author intends to find out Erdogan's construct of Islamism in this normalization and the extent of the relationship between the two. This study used descriptive qualitative methods with secondary sources as references. With Constructivism Theory and the Concept of Al-Wala wa Al-Bara from Sayyid Qutb's perspective, this study finds the construct of Islamism in the policy: First, this normalization does not exclude Erdogan from Al-Wala's aqeedah with the limitations of Al-Bara from Sayyid Qutb's perspective; Second, the relationship between Türkiye and Israel does not enter into the realm of aqeedah, but is a matter of akhlaq where Türkiye does not sacrifice its devotion and loyalty because the cooperation between the two countries is in the economic field. In addition, this normalization focuses on Islamic interests in Palestine, especially the struggle towards Baitul Maqdis and humanitarian interests for the people of Gaza; Third, in the normalization policy, Türkiye has a strategy to identify the Islamic community with Strategic Depth and overcome Western hegemony in the region around Türkiye and; Fourth, the implementation of the Al-Wala wa Al-Bara Concept in Turkish foreign policy does not contradict Sayyid Qutb's views on contemporary doctrines such as Nationalism, Patriotism, Humanity, and Secularism. The author then finds that there is a symbiotic relationship between religion and the state as well as the presence of mas'uliyyah in leadership on earth which provides benchmarks or limits for normalization: First, this normalization is limited by Erdogan's Islamic aqeedah with his defense of Palestine and; Second, cooperation between the two countries is established as long as there is a fulfillment of the needs of the Turkish people.